Multicultural Education to Improve Social Skills and Globally Competitive Human Resources - Haratua, Chandra Sagul; Suyono, Imam; Prasetio, Akbar Caesar; Susantadiredja, Abed Mesah; Panjaitan, Mikal (Candradimuka: Journal of Education, 2025)
The purpose of this study is to explore the role of multicultural education in developing the social and interpersonal competencies of human resources, and how this affects productivity and the ability to compete in the global market. Methods This research used a qualitative approach. The type of research used is descriptive-exploratory, which aims to describe how multicultural education is implemented in formal education and explore its impact on the social abilities and cross-cultural skills of human resources. The result of this research is that multicultural education in Indonesia plays an important role in building the social skills and competencies of human resources who are ready to compete at the global level. This approach includes respect for diversity, implementation of inclusive learning, and development of social skills such as empathy, intercultural communication, and cooperation in diverse teams. Research findings show that multicultural education improves cultural adaptation, critical thinking and professional readiness in a multicultural global work environment. Despite its benefits, its implementation faces challenges such as teachers' lack of understanding and the existence of stereotypes and discrimination.